Conceptualization of Bioactive Materials in Dental Caries Prevention - Govind, Shashirekha; Jena, Amit; Mohanty, Neeta; Kamilla, Sushanta Kumar (Siriraj Medical Journal, 2021)
Clinicians always face a challenge in selecting the appropriate material for clinical use. Presently, the term bioactive is being used judiciously and unquestionably in the field of dental materials. The introduction of nanotechnology brought about a revolution in material science leading to the development of bioactive materials for caries prevention and management. This review comprehensively evaluates the use of bioactive materials for modification of the oral biome, prevention of dental caries, and the management of dental caries as restorative materials. Six online database (PubMed, Scopus, Science Direct, Embase, Web of Science, and Cochrane library) were systematically searched using broad keywords. Published articles were scrutinized, analyzed and the full-text articles were selected. Data reveals relatively limited application of tissue engineering and regeneration for enamel and dentin due to their limited ability to remodel. However, many steps are being taken in biomimetic approach for the modification of dentin. The path to overcoming any challenges will require active collaboration among clinicians, a material scientist and pulp biologist.